Tardive Dyskinesia, Oral Parafunction, and Implant-Supported Rehabilitation. (6th December 2016) - Lumetti, S.; Ghiacci, G.; Macaluso, G. M.; Amore, M.; Galli, C.; Calciolari, E.; Manfredi, E.
Abstract : Oral movement disorders may lead to prosthesis and implant failure due to excessive loading. We report on an edentulous patient suffering from drug-induced tardive dyskinesia (TD) and oral parafunction (OP) rehabilitated with implant-supported screw-retained prostheses. The frequency and intensity of the movements were high, and no pharmacological intervention was possible. Moreover, the patient refused night-time splint therapy. A series of implant and prosthetic failures were experienced. Implant failures were all in the maxilla and stopped when a rigid titanium structure was placed to connect implants. Ad hoc designed studies are desirable to elucidate the mutual influence between oral movement disorders and implant-supported rehabilitation.